Anti-Cancerous, Anti-Tumour, Anti- Carcinogenic agents - Herbal Medicinal Plants and their immense pharmacological, therapeutics medicinal potent values - Sagar, Pawan Kumar; Candra, Harish; Sagar, Aditya; S, Sajwan; Murugeswaran, R (Asian Journal of Pharmaceutical Research and Development, 2025)
At present Cancer and Tumor is a common disease and very badly affected to a large number of world population masses. Various modern medical, scientific research and treatment are available to treat Human cancer and tumor now a days. Some of them are very useful and some show many toxic, hazardous and harmful effects upon treated Human cells. At present natural occurring resources substances like herbal, medicinal plant based drugs are trending, discovered of very effected novel drug development bioactive marker compounds for the treatment of every type of illness and diseases. These are non-toxic and give us maximum efficacy and safety. In this review paper, we can studies of Pharmacological, bioactive phytochemical constituents, therapeutic uses, medicinal potent values of herbal Anti-Cancerous, Anti-Tumour’s, Anti-Carcinogenic and Anti-Cytotoxic 32 species single medicinal plants which are remains a significant challenging task on global levels, explored and available in Asian and southern, northern Himalayan region on the basis of Google search engine databases. These are some 32 species herbal medicinal plants used to treat and cure of various therapeutic illness of public mankind from since ancient time. This review study aims to evaluate, numerous remarkable potent anticancerou’s, antitumor’s, anticarnogenic activities commonly both In-vitro and In-vivo, due to the presence of Alkaloids, flavonoids, steroidal, glycosides, terpenoids, tannin, phenolic, saponins, lignin’s, proteins and phenolic acids, Anti-cancer’s and Anti-tumor’s major bioactive compounds. However, more research is needed to explore the In-vivo clinical evaluation for their future’s uses, application in treating various ailments for beneficial to public, mankind. Keywords: Anticancer’s, Antitumor’s, Anti-Carcinogenic agent, bioactive phytochemical constituents, Pharmacological, and therapeutic medicinal potential values, electronic Google search engine databases.